5G NR Network Planning Analysis using 700 Mhz and 2.3 Ghz Frequency in The Jababeka Industrial Area - Achmad Kirang; Alfin Hikmaturokhman; Khoirun Ni'amah (Universitas Medan Area, 2023)
This research designed a 5G NR network using 700 MHz and 2.3 GHz frequencies with 30 MHz bandwidth in the Jababeka industrial area covering an area of 5600 hectares. The Propagation Model used by Urban Macrocell (UMa) in non line of sight (NLOS) conditions according to 3GPP TR 38901 standard with Synchronization signal-reference signal received power (SS-RSRP) and Synchronization Signal to Interference and Noise Ratio (SS-SINR) parameters. Coverage prediction simulation using Atoll 3.4 consists of 4 scenarios. Scenario 1 uses a frequency of 2.3 GHz downlink, scenario 2 uses a frequency of 2.3 GHz uplink, scenario 3 uses a frequency of 700 MHz downlink and scenario 4 uses a frequency of 700 MHz uplink. Parameters analyzed were signal strength (SS-RSRP > -110 dBm) and signal quality (SS-SINR > 5 dB). The simulation results of scenario 1 get a signal strength of 61% and signal quality of 73.71% from the Jababeka area. Scenario 2 gets 100% for signal strength and 75.35% for signal quality. Scenario 3 gets a signal strength of 72.27% and signal quality of 85.30%. Scenario 4 shows a signal strength of 100% and signal quality of 71.04% from the Jababeka area. Planning with a frequency of 700 MHz shows that the signal strength and signal strength parameters are better than the 2.3 GHz frequency, making it suitable for 5G networks in the Jababeka area. The findings of this study are intended to help Indonesian cellular operators plan and deploy their 5G network.